Effect of Supplementation of Buffer salt on Milk Production in Dairy cows - P. Suresh Kumar (The Indian Veterinary Journal, 2024)
Alteration in feeding methods by addition of buffer salt (Sodium bicarbonate) alters the rumen pH and improves rumen microbial population which in turn enhances the milk yield and milk quality. Hence Krishi Vigyan Kendra, Kancheepuram, District, Tamil Nadu, conducted a nutritional management practice of proven methods to enhance the production and productivity in dairy cattle during the year 2007.Two technologies on feed additives (T1) which included Sodium bicarbonate @ 2%, of concentrate mixture and (T2) as Farmers practice were demonstrated it was evident that supplement of bicarbonate had superior effect on burning the excess acid in rumen and prevented the accumulation of lactate and allowed better fiber digestion by strengthening reducing condition of ruminal environment.